An offline prediction of nanoscale ripples propagation under ion irradiation: A correlation between ripples velocity and surface erosion rate. (January 2021) - Panchal, Vandana; Kumar, Tanuj; Sulania, Indra; Kumar, Shyam
Abstract: An offline measurement of surface ripples propagation has been proposed using sequential ion beam irradiation approach. First, the ripple patterns were grown on Si (100) using 100 keV Ar + at a fluence of 9 × 10 17 ions/cm 2 and then subsequent second stage irradiation was performed on partially masked rippled surface to study the ripple's propagation and surface erosion. Offline atomic force microscopy (AFM) study shows that with increase in fluence from 3 × 10 17 ions/cm 2 to 7 × 10 17 ions/cm 2, in second stage irradiation, the ripples are found to propagate along the projection of the ion beam's incident direction onto the surface. This observation of ripples propagation contradicts several existing models for ion-beam-induced ripple development. Furthermore, surface erosion rate due to sputtering was measured using stylus profilometer. A prediction of relation " v 0.75 v o " between ripple's propagation velocity ( v ) and surface erosion rate ( v o ) shows the importance of Navier-Stokes viscous flow in near surface layer for the evolution of ripple patterns under ion beam irradiation (IBI). Highlights: A new approach of measuring ripples velocity in offline mode. First time measurement of surface erosion rate using offline atomic force microscopy and stylus profilometer. Correlation between ripples propagation velocity and surface erosion rate. Experimental evidence of Navier stokes flow in ripples propagation.